Telehealth and occupational therapy in early intervention - American Occupational Therapy Association (North Bethesda, MD American Occupational Therapy Association, 2022)
As telehealth and virtual instruction in schools become commonplace, occupational therapy practitioners have the opportunity to apply their flexibility, adaptability, and unique skill set to serve students in schools, regardless of physical location. This text, the first in a series on telehealth by AOTA, acknowledges that telehealth is a critical part of school-based occupational therapy. It equips practitioners to effectively bridge the digital divide, ensure equitable access to services, determine whether telehealth is an appropriate fit, and work with caregivers for the best possible outcomes. Case examples illustrate how to apply content in realistic scenarios. Practical and evidence based, practitioners can immediately integrate information into their occupational therapy practice to support students and participation in school"--Publisher's description.
Equity considerations for telehealth in schools -- Best practices in providing telehealth to support participation in school -- Telehealth evaluation and assessment in schools -- Supporting student self-regulation in telehealth -- Implementing interventions in schools through telehealth -- Coaching and supporting caregivers via telehealth -- Appendices. Telehealth in occupational therapy. -- Guidelines for occupational therapy in early intervention -- Legal, ethical, and procedural considerations.
Includes bibliographic references and index.
Keywords: Occupational therapy for children -- United States; Occupational therapy services -- United States; School health services -- United States; Telecommunication in medicine -- United States